Teach For America influence on non-TFA teachers in TFA-hiring schools - Anderson, Ashlee; Thomas, Matthew A. M.; Brewer, T. Jameson (Education Policy Analysis Archives, 2022)
Teach For America (TFA) has left an indelible mark on education in the United States and worldwide through its expansion via Teach For All. A considerable body of research examines the impact and experiences of teachers who enter the profession via TFA and related organizations, including the ways in which they embody controversial policies and new forms of teacher expertise and professionalism. Scant research, however, has examined the experiences of non-TFA teachers who work alongside them. This instrumental case study draws on interviews with nine non-TFA teachers working in traditional public schools to explore their experiences of interacting with TFA teachers at their schools. The findings focus on the perceived inexperience of TFA teachers as well as the labor expended by non-TFA teachers in support of these novice teachers. The paper also examines experiences of TFA teacher attrition and its impact on other teachers, students, and staff at the schools. The paper concludes by discussing the significance of this study and related research across individual, institutional, and broader structural levels.